2004
DOI: 10.1021/bp030050i
|View full text |Cite
|
Sign up to set email alerts
|

On‐Line Sterilization of Cheese Whey Using Ultraviolet Radiation

Abstract: The effectiveness of ultraviolet radiation for on-line sterilization of cheese whey was investigated. The effects of flow rate and residence time on the performance of three UV reactors having different gap sizes (18, 13, and 6 mm) were studied. Six flow rates and six residence times were tested with the three UV reactors. The cheese whey used in this study had a very high turbidity (4317 NTU), very poor transmittance in the UV radiation germicidal range ( approximately 0%), and high percentage of large solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Cairns [44] proposed fouling to be a net process of loading and removal of UV absorbing organics and/or organics present in the liquid medium and suggested adsorption as one mechanism of fouling. While using cheese whey for online sterilization, Mahmoud and Ghaly [17] found a rubber like material on the quartz tube, which was morphologically homogeneous and consistent along whole lamp. They related lamp fouling to the increases in the cheese whey temperature.…”
Section: Flow Characteristicsmentioning
confidence: 96%
See 4 more Smart Citations
“…Cairns [44] proposed fouling to be a net process of loading and removal of UV absorbing organics and/or organics present in the liquid medium and suggested adsorption as one mechanism of fouling. While using cheese whey for online sterilization, Mahmoud and Ghaly [17] found a rubber like material on the quartz tube, which was morphologically homogeneous and consistent along whole lamp. They related lamp fouling to the increases in the cheese whey temperature.…”
Section: Flow Characteristicsmentioning
confidence: 96%
“…McDonald et al [29] stated that liquid in the UV reactor must have sufficient residence time and turbulent mixing to achieve dose equilibrium. Mahmoud and Ghaly [17] while sterilizing cheese whey by UV found that the cell removal efficiency increased with increase in residence time (decrease in flow rate). The destruction efficiency in the single coil reactor increased from 60.77% at the flow rate of 5 mL/min (168 min residence time) to 99.98% at the flow rate of 30 mL/min (a 28 min residence time) and then decreased with increases in the flow rate reaching 46.2% at the flow rate of 70 mL/min (a 12 min residence time).…”
Section: Microbial Survivalmentioning
confidence: 99%
See 3 more Smart Citations